Women’s economic empowerment and leadership: Examining an intervention for smallholder farmers delivered via farmer producer organizations in Guatemala using qualitative methods - Myers, Emily; Heckert, Jessica (International Food Policy Research Institute, 2025)
Women work across multiple nodes in agricultural value chains, though their participation in value chains varies within and across contexts and their contributions are often underrecognized (Malapit et al., 2020; Quisumbing et al., 2021). Addressing issues such as weak economic growth, climate change, and hunger will require strengthening agricultural value chains, though doing so without a gender-sensitive lens may exacerbate existing gender inequalities within them (Rubin & Manfre, 2014). Development practitioners seeking to strengthen agricultural value chains are increasingly interested in programs that use group-based approaches, as they may reach many people efficiently using such a strategy. However, there is not much evidence on how to increase women’s economic opportunities in agricultural value chains and bolster women’s leadership within the context of group-based interventions.